On the universality of the attribution‐affect model of helping. (23rd February 2015) - Reisenzein, Rainer
<x xml:space="preserve">Abstract</x> Although Pilati et al.'s (2014) findings question the strong quantitative universality of the attribution‐affect model of helping, they are consistent with a weak form of quantitative universality, as well as with the qualitative universality of the theory. However, universality is put into question by previous studies revealing significant and sizeable between‐study differences in the strength of the causal paths postulated by the theory. These differences may in part reflect differences in the type of helping situations studied.